Transcatheter closure of a rare coronary artery fistula using a modified mother-child technique - Catarina Perez-Brandao; António Fiarresga; Lídia Sousa; José D Martins (Wolters Kluwer Medknow Publications, 2019)
Coronary artery fistulas (CAFs) are rare abnormal communications between a normal coronary artery and a cardiac chamber or great vessel, such as the pulmonary artery, bypassing the myocardial capillary network. We report the case of a 17-year-old male with a medical history of pulmonary valve stenosis, who presented with progressive dyspnea and fatigue. Transthoracic Doppler echocardiography showed multiple continuous flows both on the apical interventricular septum and entering the left atrium. A tortuous CAF arising from the left main coronary artery to the left atrium was revealed by coronary angiography. The lesion was successfully closed percutaneously using an off-label Amplatzer™ Duct Occluder II Additional Sizes with a backup support of a modified "mother-child" system. This case highlights the effort of both pediatric and adult cardiology teams to come up with new potential strategies and combined techniques to overcome the difficulties of managing complicated CAFs, such as the use of percutaneous coronary intervention techniques and the selection of the most adequate occlusion devices, even when used off-label.